2021
DOI: 10.1080/17510694.2021.1912536
|View full text |Cite
|
Sign up to set email alerts
|

Art toy as a tool for engaging the global public on the city of Surabaya

Abstract: Art toys, often called designer toys, are three-dimensional figures of hybrid and stylised characters that are reproduced and commonly customised in limited quantities and sold among segmented hobbyists and collectors. Within this niche, however, there is an unexplored territory of art toy character design that is based on a city's symbols. Such is the case with the city emblem of Surabaya, Indonesia, which already has the iconic images of a shark and a crocodile (Suro and Boyo). As Surabaya continuously focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…For instance, Torres and Macedo (2000) developed a card game to create awareness of and explore attitudes toward environmental conservation and urban development [49]. More recently, Kuntjara (2022) found that art toys based on the city's symbols were a potential platform and asset for engaging the public for Surabaya in Indonesia [50].…”
Section: Sustainability For Peripheral Areas Via Cultural Innovationmentioning
confidence: 99%
“…For instance, Torres and Macedo (2000) developed a card game to create awareness of and explore attitudes toward environmental conservation and urban development [49]. More recently, Kuntjara (2022) found that art toys based on the city's symbols were a potential platform and asset for engaging the public for Surabaya in Indonesia [50].…”
Section: Sustainability For Peripheral Areas Via Cultural Innovationmentioning
confidence: 99%